2004
DOI: 10.1074/jbc.m314037200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Signal Transducer and Activator of Transcription 3 Binding to Phosphotyrosine Ligands Containing the YXXQ Motif

Abstract: Stat3 is an Src homology (SH)2-containing protein constitutively activated in a wide variety of human cancers following its recruitment to YXXQ-containing motifs, which results in resistance to apoptosis. Despite resolution of the crystal structure of Stat3 homodimer bound to DNA, the structural basis for the unique specificity of Stat3 SH2 for YXXQ-containing phosphopeptides remains unresolved. We tested three models of this interaction based on computational analysis of available structures and sequence alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 43 publications
(38 reference statements)
2
48
0
Order By: Relevance
“…Similar computational analysis has been applied in the development of inhibitors of Stat3 and other proteins (14,15). The docking pose of S3I-201 suggests that its aminosalicylic moiety mimics the phenylphosphate group of the PpYLKT motif.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar computational analysis has been applied in the development of inhibitors of Stat3 and other proteins (14,15). The docking pose of S3I-201 suggests that its aminosalicylic moiety mimics the phenylphosphate group of the PpYLKT motif.…”
Section: Discussionmentioning
confidence: 99%
“…Stat3 dimerization relies on the reciprocal binding of the SH2 domain of one monomer to the Pro-pTyr-Leu-Lys-Thr-Lys sequence of the other Stat3 monomer. To pursue the development of inhibitors of Stat3 signaling, key structural information gleaned from the x-ray crystal structure of the Stat3␤ homodimer (13) was used in the computational modeling and automated docking of small molecules into the SH2 domain of a Stat3 monomer, relative to the bound native pTyr peptide, to identify binders of the Stat3 SH2 domain, and potentially disruptors of Stat3⅐Stat3 dimers (14,15).…”
mentioning
confidence: 99%
“…3G). Examination of the protein sequence of PTPRD revealed that the cytoplasmic domain possesses 3 consensus STAT3 binding motifs (PYXXQ) (28). Moreover, knockdown of PTPRD using siRNA in both HEK 293T cells and human astrocytes results in an increase in STAT3 phosphorylation (Fig.…”
Section: Ptprd Is Mutated In Gbm and Other Human Malignanciesmentioning
confidence: 99%
“…In addition to Lck, coprecipitation of phosphorylated STAT1 and STAT3 with Lck and Tip-C484 was reported (50). A YXPQ motif of Tip (Y72; equivalent to Y114 of C488) conforms to a putative consensus binding site for STAT factors (62). Tyrosine 72 phosphorylation was required for STAT binding and transcription activation (33).…”
mentioning
confidence: 99%